Desenvolvimento dos pré-estômagos de bezerros mestiços aleitados com leite em pó associado ao soro de queijo em pó - Miranda, Maria Vivianne Freitas Gomes de (Universidade Federal Rural do Semi-Árido, 2017)
The aim of this study was to evaluate the use of whey powder associated with powdered milk as a substitute for whole milk without breastfeeding until 60 days of age on the development of pre-stomachs, growth and proliferation rate Cellular of the ruminal papillae, as well as an influence of the diets on as chymosin and pepsinogen producing cells of the calf abomasum through the immunohistochemical technique. To that end, 24 crossbred calves with one week of life were distributed in a completely randomized design with four treatments and six replicates: LI: whole milk (Control); LP: milk powder; LPS1: 80% milk powder + 20% whey powder; LPS2: 60% milk powder + 40% whey powder cheese. For the methods of dry matter (DM) consumption, measurements of hay consumption and concentrate are made by the supply / surplus method. The animals were slaughtered at 60 days of age. The cavity organs were weighed with contents, and soon thereafter emptied and newer, registering, full and empty weights, respectively. The weight of the stomach and its compartments were determined with absolute values (kg) and relative (%) as a function of the empty body weight (%PCVZ) and as a function of the weight of the whole stomach (%PE). Fragments of approximately one square centimeter (1cm2) of tissues were collected from 4 regions of the world: rumen atrium, dorsal sac, caudate-dorsal blind sac and ventral sac from where they are measured as heights of ruminal papillae. Proliferative activity was evaluated in tissue samples collected by counting Argirophilic Nucléole Organisms (AgNOR). Tissue samples of 1 cm2 of the abomasum were collected for immunohistochemistry. There was no difference for dry matter intake (P> 0.05). As averages obtained for absolute and relative weights as a function of the empty body weight of the digital compartments did not present significant residues (P> 0.05) between the treatments. Regarding the development of non-rumen papillae There were significant (P <0.05) for a height variable in the ventral sac, where animals receiving whole milk had higher averages. There were no significant differences (P> 0.05) for the rate of cell proliferation in ruminal papillae. The percentage of acini with immunoreactive cells to the chymosin and pepsinogen antibodies presented a statistical difference (P <0.05), where the calves that received a 100% whole milk diet presented a mean percentage of marking for upper chymosin (95.11%), Animals that consumed 60% milk powder + 40% whey powder (89.59%)
Keywords: Abomaso; Poligástricos; Proliferação celular; Rúmen; Abomasum; Polygastretrics; Cell proliferation; Rumen; CIENCIAS AGRARIAS::MEDICINA VETERINARIA